Terahertz wave-absorbing material, preparation method and application thereof

CN123003288APending Publication Date: 2026-10-30NANJING LUOPU TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511240677.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]因此,本发明要解决的技术问题在于克服现有技术中的太赫兹吸波材料吸收带宽窄,机械强度低,工艺成本高,环境稳定性差等缺陷,从而提供一种太赫兹吸波材料及其制备方法和应用

Benefits of technology

[0056]1.本发明提供的太赫兹吸波材料,所述太赫兹吸波材料包括碳基体和包覆碳基体表面的石墨烯量子点包覆层,所述碳基体掺杂增强体和修饰剂;所述碳基体沿内部中心到表面由介观孔>50%逐渐转变为宏观孔>70%;所述宏观孔的孔径为100-300μm,所述介观孔的孔径为1-10μm,所述%为体积占比;介观孔的梯度变化率≤20%,所述梯度变化率是指单位厚度1mm内,介观孔体积占比的下降幅度。本发明提供的太赫兹吸波材料在太赫兹频段,具有优异的吸收带宽、反射损耗、反射损耗衰减、机械强度、环境稳定性和弹性模量。太赫兹吸波材料内部的碳基体具有的宏观孔与介观孔的组合结构显著拓宽了吸波材料的吸收带宽、降低了反射损耗和反射损耗衰减,从而拓宽了太赫兹吸波材料在太赫兹频段的吸收带宽,碳基体掺杂的修饰剂和增强体通过化学键和界面显著提升太赫兹吸波材料的机械强度;表面包覆的石墨烯量子点具有较好的量子效应,与增强体形成的界面化学键合,有效提升了太赫兹吸波材料的机械强度、环境稳定性和弹性模量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005578758010000141
    Figure BDA0005578758010000141
  • Figure BDA0005578758010000142
    Figure BDA0005578758010000142
  • Figure BDA0005578758010000151
    Figure BDA0005578758010000151
Patent Text Reader

Abstract

The application belongs to the field of terahertz materials, and particularly relates to a terahertz wave absorbing material, a preparation method and application thereof. The application provides a terahertz wave absorbing material, which comprises a carbon base and a graphene quantum dot coating layer covering the surface of the carbon base, and the carbon base is doped with a reinforcing body and a modifier; the carbon base gradually changes from mesoporous holes > 50% to macro-porous holes > 70% from the inside center to the surface; the pore diameter of the macro-porous holes is 100-300 mu m, the pore diameter of the mesoporous holes is 1-10 mu m, and the % is a volume ratio; the gradient change rate of the mesoporous holes is less than or equal to 20%, and the gradient change rate refers to the decline amplitude of the volume ratio of the mesoporous holes in a unit thickness of 1 mm. The terahertz wave absorbing material provided by the application has excellent absorption bandwidth, reflection loss, reflection loss attenuation, pressure strength and elastic modulus in the terahertz frequency band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of terahertz materials, specifically relating to a terahertz absorbing material, its preparation method, and its application. Background Technology

[0002] Existing terahertz absorbing materials are mainly mesophase pitch-based carbon foam and MXenes / graphene composite foam. Carbon foam with a single pore size (50-200μm) is graphitized to improve its conductivity loss capability, but it has a narrow absorption bandwidth, low mechanical strength, high process cost, and poor environmental stability. Summary of the Invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing terahertz absorbing materials, such as narrow absorption bandwidth, low mechanical strength, high processing cost, and poor environmental stability, so as to provide a terahertz absorbing material, its preparation method and application.

[0004] To this end, the present invention provides the following technical solution.

[0005] This invention provides a terahertz absorbing material, which includes a carbon matrix and a graphene quantum dot coating layer covering the surface of the carbon matrix, wherein the carbon matrix is ​​doped with a reinforcing agent and a modifier;

[0006] The carbon matrix gradually changes from mesopores > 50% to macropores > 70% from its internal center to its surface; the macropores have a diameter of 100-300 μm, the mesopores have a diameter of 1-10 μm, and the percentage is a volume percentage.

[0007] The gradient change rate of mesopores is ≤20%, where the gradient change rate refers to the decrease in the proportion of mesopore volume within a unit thickness of 1 mm.

[0008] The terahertz absorbing material provided by this invention forms a dual-mode pore size distribution, with macroscopic and mesoscopic pores combining to effectively improve the absorption bandwidth, mechanical strength, and environmental stability of the absorbing material. The graphene quantum dot coating on the carbon matrix surface creates a quantum tunneling effect, significantly improving conductivity and thus broadening the absorption bandwidth. Furthermore, the graphene quantum dot coating reduces heat accumulation and inhibits oxidation, thereby enhancing the environmental stability of the terahertz absorbing material. Simply increasing the amount of silicon carbide without a graphene quantum dot coating does not improve conductivity.

[0009] In one alternative embodiment, the thickness of the graphene quantum dot coating is 50-200 nm.

[0010] In one optional embodiment, the graphene quantum dot coating layer includes a first graphene quantum dot, the first graphene quantum dot having a particle size of 1-5 nm.

[0011] In one alternative embodiment, the mass ratio of the carbon matrix, the reinforcing agent, and the modifier is (40-60):(5-15):(1-5).

[0012] In one alternative embodiment, the reinforcing material comprises at least one of silicon carbide, carbon fiber, graphene, and boron nitride.

[0013] In one optional embodiment, the reinforcing body includes silicon carbide, wherein the silicon carbide is silicon carbide nanowire; preferably, the diameter of the silicon carbide nanowire is 20-200 nm, which can further improve the mechanical strength and absorption bandwidth of the terahertz absorbing material; if the diameter of the silicon carbide nanowire is >200 nm, it will reduce the interfacial bonding force, and <20 nm will easily agglomerate, thereby affecting the performance of the terahertz absorbing material; preferably, the aspect ratio of the silicon carbide nanowire is >100; using this aspect ratio can effectively improve the mechanical interlocking effect, thereby improving the mechanical strength of the terahertz absorbing material; preferably, the length of the silicon carbide nanowire is 2-5 μm.

[0014] In one optional embodiment, the reinforcement comprises the carbon fiber, preferably with a length of 50-200 μm; preferably, the mass ratio of the carbon matrix to the carbon fiber is (40-60):(5-8); this can optimize the stress distribution of the terahertz absorbing material, thereby improving its compressive strength.

[0015] In one alternative embodiment, the boron nitride comprises boron nitride nanosheets.

[0016] In one alternative embodiment, the graphene comprises graphene nanosheets having the following parameters: number of layers ≤ 3 layers, sheet diameter ≤ 5 μm.

[0017] In one alternative embodiment, the modifier includes at least one of a second graphene quantum dot and silver nanowires.

[0018] When the modifier is second graphene quantum dots and the reinforcing agent is silicon carbide nanowires, the silicon carbide nanowires and second graphene quantum dots are connected by ester bonds, and the silicon carbide nanowires and carbon matrix are connected by a carbon network, forming a chemically bonded interface, which greatly improves the shear strength. If silicon carbide nanowires are not doped internally, the second graphene quantum dots and carbon matrix are only physically adsorbed together, resulting in poor shear strength.

[0019] In one alternative embodiment, the particle size of the second graphene quantum dot is ≤10nm.

[0020] In one optional embodiment, the modifier comprises the silver nanowires, wherein the mass ratio of the carbon matrix to the silver nanowires is (40-60):(1-3); preferably, the diameter of the silver nanowires is ≤50nm; preferably, the length of the silver nanowires is ≤1μm.

[0021] Preferably, the silver nanowires have a coating layer on their surface; preferably, the coating layer comprises silicon dioxide; preferably, the thickness of the coating layer is 5-10 nm; preferably, the coverage of the coating layer is ≥90%.

[0022] In one optional embodiment, the carbon matrix is ​​further doped with carbon nanotubes; preferably, the length of the carbon nanotubes is ≤1 μm; preferably, the mass ratio of the carbon nanotubes to the modifier is (1-3):(1-5).

[0023] This invention also provides a method for preparing a terahertz absorbing material, comprising the following steps:

[0024] The carbon source, reinforcement and modifier are mixed, heated to foam, gradient sintered, and then vapor-deposited by introducing carbon source gas to obtain terahertz absorbing material.

[0025] In one alternative embodiment, the carbon source includes at least one of bitumen and a polymer.

[0026] In one alternative embodiment, the carbon source comprises bitumen, and the mass ratio of bitumen, reinforcement and modifier is (40-60):(5-15):(1-5).

[0027] In an optional embodiment, the mixing further includes the addition of at least one of a binder and an antioxidant; preferably, the binder includes at least one of polyimide and phenolic resin; the addition of the binder can further promote the uniform dispersion of the carbon source, reinforcement, and modifier, suppress bubble coalescence, and give the prepared terahertz absorbing material a porous structure, thereby improving the absorption bandwidth, mechanical strength, and environmental stability of the terahertz absorbing material; preferably, the mass ratio of the binder to the modifier is (0-10):(1-5).

[0028] Preferably, the antioxidant includes boron nitride; boron nitride as an antioxidant can improve the chemical stability of terahertz absorbing materials under high temperature and high humidity conditions. Preferably, the boron nitride includes boron nitride nanosheets; when using boron nitride nanosheets as an oxidant, it has the following advantages: (1) The boron nitride nanosheets partially form a discontinuous coating layer on the surface of the carbon ligament, which together with the graphene quantum dot coating layer isolates oxygen or water vapor penetration, reducing the oxidation rate by 80%; under an environment of 150℃ / 60% humidity, the absorption performance decays by ≤3% within 30 days. (2) The boron nitride nanosheets have high thermal conductivity, which can promote uniform heat diffusion and avoid pore structure distortion caused by local overheating; in the terahertz band, the dielectric constant of the boron nitride nanosheets matches that of the carbon matrix, reducing electromagnetic wave reflection and improving impedance matching; the boron nitride nanosheets and silicon carbide nanowires form a bidirectional thermally conductive network, improving the thermal stability of the terahertz absorbing material. (3) Boron nitride nanosheets are embedded in the carbon ligaments, inhibiting crack propagation and improving compressive strength through a pinning effect. Preferably, the mass ratio of the antioxidant to the modifier is (0-3):(1-5).

[0029] When antioxidants and binders are added simultaneously to prepare terahertz absorbing materials, the frequency band of the terahertz absorbing materials can be extended. The carbon skeleton remaining after polyimide is sintered as a binder will also form a conductive-thermal insulating dual network with the antioxidant boron nitride nanosheets. While improving conductivity, the high thermal conductivity (830 W / (m·K)) within the boron nitride nanosheets rapidly dissipates heat, while the low thermal conductivity (2 W / (m·K)) outside the surface provides thermal insulation, effectively balancing electrical conductivity and thermal stability.

[0030] In one alternative embodiment, the polymer comprises at least one of polyimide and cyanate resin.

[0031] In one alternative embodiment, the carbon source comprises cyanate resin, wherein the mass ratio of the cyanate resin, the reinforcing agent, and the modifier is (66-100):(5-15):(1-5).

[0032] In one optional embodiment, the polymer comprises cyanate resin and is foamed using a microporous mold; this allows thermal decomposition gases (HCN / NH3) to be directionally discharged through the micropores, preventing the pore structure from breaking. This affects the mechanical and absorption properties of the terahertz absorbing material. The parameters of the microporous mold include micropore channels with a pore size of 10-50 μm and a channel density ≥20 channels / cm². 2 .

[0033] In one optional embodiment, the polymer comprises polyimide, and the binder is added after mixing; preferably, the carbon source comprises polyimide, and the mass ratio of the polyimide, the reinforcing agent, and the modifier is (66-100):15:(1-5).

[0034] In an optional embodiment, when the reinforcement comprises carbon fibers, the carbon fibers are preferably surface-carboxylated; preferably, the density of surface carboxyl groups is ≥3 groups / nm. 2 Preferably, the density of surface carboxyl groups is ≥4 groups / nm. 2 Controlling the density of carboxyl groups on the carbon fiber surface, especially preferably ≥4 groups / nm. 2 This allows the carbon fibers to be evenly dispersed, helping to build a pre-bonded interface and optimize the foaming structure, thereby improving the mechanical strength of the terahertz absorbing material and broadening the absorption bandwidth.

[0035] In one optional embodiment, when the carbon matrix is ​​doped with carbon nanotubes, the carbon nanotubes are preferably surface-carboxylated; preferably, the density of the surface carboxyl groups is ≥3 groups / nm. 2 The density of the surface carboxyl groups is ≥3 groups / nm. 2 The density of surface carboxyl groups can be increased by combining a strong oxidation system with ultrasound.

[0036] In one alternative embodiment, the heating is carried out at atmospheric pressure; atmospheric pressure foaming can prevent defects such as microcracks or delamination, thereby improving the pressure resistance of the terahertz absorbing material. In addition, atmospheric pressure conditions have low process requirements and effectively reduce process costs.

[0037] In one alternative embodiment, the heating is performed under a nitrogen atmosphere.

[0038] In one alternative embodiment, the heating temperature is 280-320°C.

[0039] In one alternative embodiment, the heating time is 30-40 minutes.

[0040] When polyimide is used as the carbon source, it will pyrolyze during sintering to generate nitrogen-containing gas, forming a microporous structure and enhancing the multiple reflection paths of electromagnetic waves. The carbon skeleton remaining after sintering forms a covalent bond with the carbon matrix formed by the carbon source, enhancing the ligament strength. The thermal decomposition temperature of polyimide (>500℃) is higher than the foaming temperature, avoiding premature decomposition of polyimide during the heating and foaming stage, which would lead to the collapse of the pore structure.

[0041] In one optional embodiment, the gradient sintering includes a first sintering and a second sintering; the segmented sintering provided by the present invention utilizes the temperature-shrinkage difference of the raw materials to give the terahertz absorbing material a dual-mode pore size distribution structure, thereby giving it excellent absorption bandwidth, mechanical strength and environmental stability.

[0042] Preferably, the temperature of the first sintering is 800-1000℃;

[0043] Preferably, the first sintering time is 1-3 hours;

[0044] Preferably, the heating rate of the first sintering is 4-5℃ / min.

[0045] Preferably, the second sintering temperature is 1600-2000℃;

[0046] Preferably, the second sintering time is 2-3 hours;

[0047] Preferably, the heating rate of the second sintering is 10-15℃ / min.

[0048] Existing technologies for preparing terahertz absorbing materials involve high-temperature reduction with hydrogen to remove oxygen-containing end groups, repair lattice defects, and restore the continuity of the carbon network, thereby improving conductivity. However, the absorbing materials are prone to microcracks at high temperatures, and the process is complex. Furthermore, the resulting terahertz absorbing materials have poor environmental stability. The terahertz absorbing materials prepared using the method provided in this invention have a simple process, good environmental stability, high shear strength, and good structural stability. They are also less prone to microcracks at high temperatures.

[0049] Furthermore, the reinforcing phase and modifier selected in this invention will not decompose under gradient sintering. Sintering will further optimize the crystal structure of the reinforcing phase and modifier, better generate synergistic effects, and improve the absorption performance of the terahertz absorbing material.

[0050] When graphene nanosheets are used as reinforcement, after gradient sintering and cooling to 400-800℃, a nickel catalyst layer is pre-deposited on the surface of the carbonized foam, followed by vapor deposition. The parameters of the nickel catalyst layer include: thickness 50-100 nm, lattice density ≥100 particles / mm². 2 The nickel catalyst can be any conventionally selected in the art, and the present invention does not make any limitation. As an example, the nickel catalyst layer can be obtained by magnetron sputtering or electron beam evaporation deposition of pure nickel nanoparticles.

[0051] In one alternative embodiment, the carbon source gas includes methane; methane is selected for vapor phase deposition to form a graphene quantum dot coating layer.

[0052] Preferably, the flow rate of the carbon source gas is 50-60 sccm.

[0053] Preferably, the vapor deposition time is 30-40 minutes.

[0054] This invention also provides the application of the above-mentioned terahertz absorbing material or the terahertz absorbing material prepared by the above-mentioned method in terahertz communication and radar stealth.

[0055] The technical solution of this invention has the following advantages:

[0056] 1. The terahertz absorbing material provided by this invention comprises a carbon matrix and a graphene quantum dot coating layer covering the surface of the carbon matrix. The carbon matrix is ​​doped with a reinforcing agent and a modifier. The carbon matrix gradually transitions from mesopores > 50% to macropores > 70% from its internal center to its surface. The macropores have a diameter of 100-300 μm, and the mesopores have a diameter of 1-10 μm. The percentage represents the volume percentage. The gradient change rate of the mesopores is ≤ 20%, where the gradient change rate refers to the decrease in the volume percentage of mesopores within a unit thickness of 1 mm. The terahertz absorbing material provided by this invention exhibits excellent absorption bandwidth, reflection loss, reflection loss attenuation, mechanical strength, environmental stability, and elastic modulus in the terahertz frequency band. The combination of macroscopic and mesoscopic pores in the carbon matrix of terahertz absorbing materials significantly broadens the absorption bandwidth and reduces reflection loss and attenuation, thereby widening the absorption bandwidth of terahertz absorbing materials in the terahertz frequency band. The modifiers and reinforcements doped in the carbon matrix significantly improve the mechanical strength of terahertz absorbing materials through chemical bonds and interfaces. The graphene quantum dots coated on the surface have good quantum effects and form chemical bonds with the interface of the reinforcement, effectively improving the mechanical strength, environmental stability and elastic modulus of terahertz absorbing materials.

[0057] 2. In the terahertz absorbing material provided by the present invention, when silicon carbide nanowires are used as the reinforcing body, a coherent interface is formed with the carbon matrix, which uniformly disperses the local stress to the overall structure and improves the mechanical strength of the terahertz absorbing material.

[0058] The silicon carbide nanowires and graphene quantum dot coatings have a good synergistic effect: (1) The first graphene quantum dots and silicon carbide nanowires form a large number of heterojunctions at the interface through ester bonds, which induces the accumulation of interface charge when electromagnetic waves are incident, significantly improving the dielectric loss, and thus significantly broadening the absorption bandwidth and reflection loss of the terahertz absorbing material. (2) The silicon carbide nanowires connect the conductive network of the graphene quantum dots on the surface and the internal carbon matrix to form a three-dimensional conductive network. (3) The graphene quantum dot coating is in the thin film state, which can effectively reduce the oxygen permeability by 80%, reduce the oxidation rate, and greatly improve the reflection loss attenuation and environmental stability of the terahertz absorbing material.

[0059] When graphene quantum dots are used as modifiers, the carbon-based doped graphene quantum dots and silicon carbide nanowires have the following advantages: (1) In the terahertz band, the surface defect states (such as oxygen vacancies) of silicon carbide nanowires will induce polarization, and cooperate with the second graphene quantum dots to perform plasmonic resonance, thereby broadening the absorption bandwidth of the terahertz absorbing material; (2) The edges of the second graphene quantum dots are modified to generate carboxyl groups, which bond with the hydroxyl groups on the surface of silicon carbide nanowires through esterification reaction, thereby improving the mechanical strength and interfacial bonding strength, and thus improving the shear strength, thereby ensuring To ensure the integrity and functional stability of the absorbing structure and avoid the degradation of absorbing performance, silicon carbide nanowires with an aspect ratio >100 are used for bridging, and second graphene quantum dots with a particle size ≤10nm are used for microcrack filling. Together with the toughening of the ester bond interface, they can further inhibit crack generation and improve the crack initiation stress, fracture toughness and compressive strength of the terahertz absorbing material; (3) The second graphene quantum dots will also fill the nano gaps between silicon carbide nanowires to inhibit microcrack initiation, thereby improving the environmental stability and mechanical strength of the terahertz absorbing material.

[0060] 3. The method for preparing terahertz absorbing materials provided by the present invention utilizes the synergistic effect of modifiers and reinforcing agents to achieve uniform bubble generation and stability under normal pressure, making it easy for industrial production. Detailed Implementation

[0061] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0062] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0063] Example 1

[0064] This embodiment provides a method for preparing a terahertz absorbing material, including the following steps:

[0065] (1) Mesophase pitch, silicon carbide nanowires (aspect ratio of 130, diameter of 100 nm) and graphene quantum dots (carboxylated graphene quantum dot powder, 10 nm, Taizhou Juna New Energy Co., Ltd.) were ball-milled at 300 rpm for 2-4 h; the mass ratio of the mesophase pitch, silicon carbide nanowires and graphene quantum dots was 40:15:1; the mixture was heated and foamed to 280 °C under a nitrogen atmosphere and held for 30 min.

[0066] (2) The temperature is increased to 800℃ at 5℃ / min for 1h, and then increased to 1800℃ at 10℃ / min for 2h; methane is introduced at a flow rate of 50sccm for vapor deposition for 30min to obtain terahertz absorbing material; in the terahertz absorbing material, the carbon matrix gradually changes from 60% mesopores to 75% macropores from the internal center to the surface, where % is the volume percentage; the gradient change rate of mesopores is 15%, the thickness of the graphene quantum dot coating layer is 80-120nm; the particle size of the first graphene quantum dot in the graphene quantum dot coating layer is 2-4nm.

[0067] Example 2

[0068] This embodiment provides a method for preparing a terahertz absorbing material, including the following steps:

[0069] (1) Cyanate resin, silicon carbide nanowires (aspect ratio 130, diameter 20nm), graphene quantum dots (carboxylated graphene quantum dot powder, 10nm, Taizhou Juna New Energy Co., Ltd.), and boron nitride nanosheets (thickness 3nm) were ball-milled at 300rpm for 3h; the mass ratio of cyanate resin, silicon carbide nanowires, graphene quantum dots, and boron nitride nanosheets was 66:10:3:1; a mold with microporous channels (micropore diameter 30μm, density 25 particles / cm) was used. 2 Heat to 300℃ under nitrogen atmosphere and hold for 30 minutes;

[0070] (2) The carbonization process is carried out at 5℃ / min to 800℃ for 2h, then at 10℃ / min to 1620℃ for 3h. Methane is introduced at a flow rate of 50sccm, and the carbonization is carried out at 1000℃ for 30min to obtain a terahertz absorbing material. In the terahertz absorbing material, the carbon matrix gradually changes from 52% mesopores to 78% macropores from the internal center to the surface. The percentage is the volume percentage. The gradient change rate of the mesopores is 18%. The gradient change rate measurement excludes the area within 2mm of the carbon matrix edge to exclude the boundary effect of the mold with microporous channels. The thickness of the graphene quantum dot coating layer is 120-150nm. The particle size of the first graphene quantum dot in the graphene quantum dot coating layer is 3.5-4.5nm.

[0071] Example 3

[0072] This embodiment provides a method for preparing a terahertz absorbing material, including the following steps:

[0073] (1) Short-cut carbon fibers (100 μm in length) were carboxylated with nitric acid, and the -COOH density reached 4 groups / nm. 2Mesophase pitch, carboxylated carbon fibers, graphene quantum dots, and boron nitride nanosheets (3 nm thick) were ball-milled at 400 rpm for 2 h; the mass ratio of the mesophase pitch, carboxylated carbon fibers, and graphene quantum dots was 60:5:5:1; the mixture was heated to 290 °C under nitrogen atmosphere and simultaneously subjected to 35 kHz ultrasonic vibration for 30 min.

[0074] (2) The temperature is increased to 800℃ at 5℃ / min for 1h, and then increased to 1800℃ at 10℃ / min for 2h; methane is introduced at a flow rate of 60sccm, and vapor deposition is carried out at 900℃ for 40min to obtain terahertz absorbing material; in the terahertz absorbing material, the carbon matrix gradually changes from 58% mesopores to 72% macropores from the internal center to the surface, where % is the volume percentage; the gradient change rate of mesopores is 15%, and the thickness of the graphene quantum dot coating layer is 60-90nm; the particle size of the first graphene quantum dot in the graphene quantum dot coating layer is 1.5-3.5nm.

[0075] Comparative Example 1

[0076] This comparative example provides a method for preparing a terahertz absorbing material, including the following steps:

[0077] (1) Mix the mesophase pitch particles with the Lewis acid catalyst at a mass ratio of 1:0.5;

[0078] (2) Place the above mixed particles in a high-pressure reactor and purge with nitrogen to a pressure of 10 MPa; raise the temperature to 400°C at 5°C / min, stop heating, and use the exothermic polymerization reaction to automatically raise the temperature to 700°C to foam; remove the foam blank after natural cooling;

[0079] (3) Heat to 1300℃ at 5℃ / min under nitrogen and hold for 2h; heat to 2500℃ at 50℃ / min under argon and hold for 15min.

[0080] Comparative Example 2

[0081] This comparative example provides a method for preparing a terahertz absorbing material, including the following steps:

[0082] (1) Graphene oxide and Ti3C2T x MXene nanosheets dispersed in water, along with graphene oxide and Ti3C2T x MXene mass ratio 1:3;

[0083] (2) Add hydrazine hydrate, foam and reduce at room temperature, release gas to form a porous structure;

[0084] (3) Freeze at -50℃ for 24 hours and vacuum dry to obtain porous foam. Reduce with hydrogen at 400℃ for 2 hours.

[0085] Comparative Example 3

[0086] This comparative example provides a method for preparing a terahertz absorbing material. The only difference from Example 1 is that silicon carbide nanowires are not added in step (1).

[0087] Comparative Example 4

[0088] This comparative example provides a method for preparing a terahertz absorbing material. The only difference from Example 1 is that graphene quantum dots are not added in step (1).

[0089] Comparative Example 5

[0090] This comparative example provides a method for preparing a terahertz absorbing material. The only difference from Example 1 is that vapor deposition is not performed in step (2), and the terahertz absorbing material does not contain a graphene quantum dot coating layer.

[0091] Test case

[0092] The performance of the terahertz absorbing materials prepared in the examples and comparative examples was tested, as follows:

[0093] (1) Absorption performance test: The number of samples fed at one time is 30. The test is carried out in accordance with GB / T30142-2013 extended to the terahertz frequency band. The average value is calculated to obtain the reflection loss, absorption bandwidth and reflection loss peak value.

[0094] (2) Mechanical performance test: The number of samples fed at one time is 30. The test is carried out according to ASTM D695, and the average value is calculated to obtain the compressive strength and elastic modulus.

[0095] (3) Yield: Calculated according to the following formula, where the number of samples per batch is 30. The results are shown in Table 1; Qualified product standards: simultaneously meet the following requirements: peak reflection loss ≤ -15dB (0.3-1.2THz band), compressive strength ≥ 40MPa, ligament thickness variation coefficient ≤ 15%, 30-day humidity decay rate ≤ 10%, and no macroscopic cracks or coating peeling;

[0096] Yield rate = (Number of qualified products / Total number of input products) × 100%.

[0097] (4) Ligament thickness variation coefficient test: 30 samples were fed at one time. The samples were brittle and fractured by liquid nitrogen. After gold sputtering, they were observed under a voltage of 5kV. Five observation areas were randomly selected on the sample surface (each observation area contains ≥20 ligaments) and the ligament diameter was measured. The ratio of the standard deviation to the mean was calculated and the mean was calculated to obtain the ligament thickness variation coefficient.

[0098] (5) Environmental stability test: Two groups of terahertz absorbing materials were tested according to GB / T30142-2013 for the first group of samples, and the humidity A0 was measured; the second group of samples were placed at 60% humidity and 150℃ for 30 days, and after cooling to room temperature, they were tested according to GB / T30142-2013 and the humidity A1 was measured; the humidity attenuation rate after 30 days = (A0-A1) / A0×100%;

[0099] Two sets of terahertz absorbing materials were tested. The first set of samples was tested according to GB / T 30142-2013 in the 0.3-1.2THz frequency band, and the reflection loss B0 was measured. The second set of samples was placed at 60% humidity and 150℃ for 30 days, and after cooling to room temperature, it was tested according to GB / T 30142-2013 in the 0.3-1.2THz frequency band, and the reflection loss B1 was measured. The reflection loss attenuation is calculated as (B0-B1) / B0×100%.

[0100] Two sets of terahertz absorbing materials were tested. The first set of samples was tested according to GB / T 30142-2013, and the absorption bandwidth C0 was measured. The second set of samples was placed at 60% humidity and 150℃ for 30 days, and after cooling to room temperature, it was tested according to GB / T 30142-2013, and the absorption bandwidth C1 was measured. The absorption bandwidth attenuation = (C0-C1) / C0×100%.

[0101] (6) Conductivity test: The test shall be conducted in accordance with GB / T 3048.2-2007.

[0102] (7) Conductivity decay test: Two sets of samples were taken. The first set of samples was tested according to GB / T 3048.2-2007, and the conductivity σ0 was measured. The second set of samples was placed at 60% humidity and 150℃ for 30 days, then transferred to a desiccator (humidity ≤40%) and placed at room temperature for 24 hours. The conductivity σ1 was measured according to GB / T 3048.2-2007. Conductivity decay = (σ0-σ1) / σ0×100%.

[0103] (8) High temperature structural stability test: a. The sample is placed on an 80℃ hot stage and a pressure of 5KPa is applied; b. The deformation-time curve is recorded, and the collapse judgment standard is: height decrease >10%; c. The collapse ratio within 30 minutes is statistically analyzed to obtain the collapse ratio at 80℃.

[0104] (9) High-frequency reflection loss test: The test was conducted according to GB / T30142-2013 extended to the terahertz band, and the reflection loss at a fixed frequency of 1.5THz was measured.

[0105] (10) High-frequency impedance matching test (extended GB / T 30142 to 2.0THz): a. Use a terahertz time-domain spectroscopy system (0.5-2.0THz); b. Measure the reflection loss in the 1.2-2.0THz frequency band; c. Extract the reflection coefficient of 1.5THz as the high-frequency representative value, calculate the impedance matching degree, and obtain the impedance matching degree of 1.5THz.

[0106] (11) Critical collapse temperature test: Set a temperature gradient from room temperature to 300℃ (gradient is: 50℃, 100℃, 150℃, 200℃, 250℃, 300℃); apply 5kPa pressure at each temperature and keep warm for 30min; monitor the deformation, and when the deformation is >10%, the collapse temperature is determined.

[0107] (12) Test of compressive strength decay rate: Take two identical samples and test the initial compressive strength (S0) of the first group according to ASTM D695; place the second group in an oven at the critical collapse temperature and keep it at the temperature for 1 hour without external pressure; after cooling to room temperature, test its compressive strength (S1);

[0108] Attenuation rate = (S0-S1) / S0×100%.

[0109] Table 1 Performance Test Results

[0110]

[0111] Table 2 Performance Test Results

[0112] Example 1 -18 (0.8 THz) 8% 3% (60% RH) Comparative Example 3 -13 (0.6 THz) 25% 12% (60% RH)

[0113] Table 3 Performance Test Results

[0114]

[0115]

[0116] Table 4 Performance Test Results

[0117]

[0118] As can be seen from the comparison of the examples and comparative examples, the terahertz absorbing material prepared by the present invention has a wide frequency band, low reflection loss and reflection loss attenuation, excellent absorption bandwidth, compressive strength and elastic modulus; the terahertz absorbing material prepared by the preparation method provided by the present invention has a high yield.

[0119] Specifically, as shown in Comparative Example 1, the existing technology uses high-pressure foaming to prepare terahertz absorbing materials. Fluctuations in foaming pressure result in uneven pore size distribution, an absorption bandwidth ≤0.5THz, uneven thickness of the prepared absorbing material, and microcracks appearing during high-pressure demolding, reducing the compressive strength to 25MPa. Furthermore, high-pressure foaming requires sophisticated equipment and generates significant energy consumption, leading to a significant decrease in yield. As shown in Comparative Example 2, the existing technology uses an MXenes / graphene composite foam structure for terahertz absorbing materials. The MXene surface end groups are easily oxidized at humidity >60%, causing a >30% decrease in conductivity and a >20% attenuation in absorption performance within 30 days. The pore walls are thin, resulting in a significantly lower compressive strength compared to the present invention, down to 18MPa, and it is prone to collapse at high temperatures (>80℃). The layered stacked structure is prone to impedance mismatch, with reflection losses >-8dB above 1.2THz.

[0120] As can be seen from Comparative Example 3, the terahertz absorbing material prepared by this invention has strong absorption capacity for electromagnetic waves and low coefficient of variation of ligament thickness (CV≤10%), indicating small fluctuations in ligament thickness, low pore structure distortion, good impedance matching performance, and good environmental stability. As can be seen from Comparative Examples 4-5, the terahertz absorbing material prepared by this invention has a wider frequency band, lower reflection loss and reflection loss attenuation, and excellent absorption bandwidth, compressive strength, and elastic modulus.

[0121] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A terahertz absorbing material, characterized in that, The terahertz absorbing material includes a carbon matrix and a graphene quantum dot coating layer covering the surface of the carbon matrix, wherein the carbon matrix is ​​doped with a reinforcing agent and a modifier; The carbon matrix gradually changes from mesopores > 50% to macropores > 70% from its internal center to its surface; the macropores have a diameter of 100-300 μm, the mesopores have a diameter of 1-10 μm, and the percentage is a volume percentage. The gradient change rate of mesopores is ≤20%, where the gradient change rate refers to the decrease in the proportion of mesopore volume within a unit thickness of 1 mm.

2. The terahertz absorbing material according to claim 1, characterized in that, The thickness of the graphene quantum dot coating layer is 50-200 nm; and / or, The graphene quantum dot coating layer includes a first graphene quantum dot, the first graphene quantum dot having a particle size of 1-5 nm; and / or, The mass ratio of the carbon matrix, reinforcing agent, and modifying agent is (40-60):(5-15):(1-5); and / or, The reinforcing material includes at least one of silicon carbide, carbon fiber, graphene, and boron nitride; and / or, The modifier includes at least one of second graphene quantum dots and silver nanowires.

3. The terahertz absorbing material according to claim 2, characterized in that, The silicon carbide includes silicon carbide nanowires; and / or, The reinforcement comprises the carbon fibers, wherein the mass ratio of the carbon matrix to the carbon fibers is (40-60):(5-8); and / or, The boron nitride comprises boron nitride nanosheets; and / or, The particle size of the second graphene quantum dot is ≤10nm; and / or, The modifier includes the silver nanowires, wherein the mass ratio of the carbon matrix to the silver nanowires is (40-60):(1-3); and / or, The carbon matrix is ​​also doped with carbon nanotubes.

4. The terahertz absorbing material according to claim 3, characterized in that, The diameter of the silicon carbide nanowires is 20-200 nm; and / or, The aspect ratio of the silicon carbide nanowires is >100; and / or, The length of the carbon nanotubes is ≤1 μm; and / or, The mass ratio of the carbon nanotubes to the modifier is (1-3):(1-5).

5. A method for preparing a terahertz absorbing material, characterized in that, Includes the following steps: The carbon source, reinforcement and modifier are mixed, heated to foam, gradient sintered, and then vapor-deposited by introducing carbon source gas to obtain terahertz absorbing material.

6. The preparation method according to claim 5, characterized in that, The carbon source includes at least one of pitch and polymer; and / or, The mixture further includes the addition of at least one of a binder and an antioxidant; and / or, The heating is performed at atmospheric pressure; and / or, The heating is carried out under a nitrogen atmosphere; and / or, The heating temperature is 280-320℃; and / or, The heating time is 30-40 minutes.

7. The preparation method according to claim 6, characterized in that, The carbon source includes asphalt, and the mass ratio of the asphalt, reinforcement, and modifier is (40-60):(5-15):(1-5); and / or, The adhesive comprises at least one of polyimide and phenolic resin; and / or, The mass ratio of the adhesive to the modifier is (0-10):(1-5); and / or, The antioxidant includes boron nitride; and / or, The mass ratio of the antioxidant to the modifier is (0-3):(1-5); and / or, The polymer includes at least one of polyimide and cyanate resin; and / or, The gradient sintering includes a first sintering and a second sintering.

8. The preparation method according to claim 7, characterized in that, The carbon source includes cyanate resin, wherein the mass ratio of the cyanate resin, the reinforcing agent, and the modifier is (66-100):(5-15):(1-5); and / or, The carbon source includes polyimide, wherein the mass ratio of the polyimide, the reinforcing agent, and the modifier is (66-100):(5-15):(1-5); and / or, The first sintering temperature is 800-1000℃; and / or, the first sintering time is 1-3 hours; and / or, the heating rate of the first sintering is 4-5℃ / min; and / or, The second sintering temperature is 1600-2000℃; and / or, the second sintering time is 2-3 hours; and / or, the heating rate of the second sintering is 10-15℃ / min; and / or, The polymer comprises polyimide, which is added to the binder after mixing; and / or, The polymer includes cyanate resin and is foamed using a microporous mold.

9. The preparation method according to any one of claims 5-8, characterized in that, The carbon source gas includes methane; and / or, The flow rate of the carbon source gas is 50-60 sccm; and / or, The vapor deposition time is 30-40 minutes.

10. The application of the terahertz absorbing material according to any one of claims 1-4 or the terahertz absorbing material prepared by any one of claims 5-9 in terahertz communication and radar stealth.